Instructional and Learning Design in Open and Distance Learning (ODL) in Higher Education. - Yusup, Hashim (2015)
With the advancement in new technologies and pedagogy in 21 Century education, you may have the choice of doing higher degree as a part-time or full-time student especially in a postgraduate programme. In this paper, the authors, sharing their experiences, argued that part-time distance learners may complete the degree full-time as long as they are able to complete the stipulated Student Learning Time (SLT) required for a degree program regardless whether they are doing full-time on campus or part-time at a distance. However, to accomplish this, ODL providers in higher education need to integrate distance learning theories, online technology and pedagogy in the instructional and learning system to enable the part-time distance learners to complete the program equivalent to full-time program. A comparison is made between part-time online distance learning and full-time blended face-to-face mode, explaining the different instructional methods and technologies used and the SLT allocated for each mode. Key words: Open and distance education; distance learning, online learning; blended learning; distance learning theories